Dietary adequacy, variety and diversity and associated factors (anthropometry and socio-economic status) in pregnant women attending the Bishop Lavis MOU in Cape Town - De Bruyn, Celeste Marinda (Division of Human Nutrition, 2016)
Includes bibliographical references